Love and let bark - Martin, Alanna (Martin, Alanna. Hearts of Alaska., 2021)
When firefighter Nate Porter returns to Helen, Alaska, with his rescue puppies in tow to prove that he is completely over his old flame Lydia Lipin, he soon realizes that he'll risk everything for a second chance as sparks fly between them.